Desenvolvimento de metodologia eletroanalítica para a determinação de cetoconazol em formulações farmacêuticas utilizando eletrodo de pasta de carbono modificado hemina. - Pitanga, ângelo Francklin (2009)
In this work electrochemical studies are broached as well the development of an analytical methodology to determinate ketoconazole in pharmaceuticals formulations with the help of electrode of carbon paste was modified with hemin. The tests were carried out in solution tampão Britton-Robinson (BR) in pH 2, with an electrode compounded by 50% of carbon past and 50% of hemin, for having the best analytical answer to the compound in question. Based on the electrochemical parameters that were taken of the technique cyclic voltammetry, differential pulse and of the square wave, it was possible diagnostic some information that was connected to the reaction mechanism such as: the reversibility of the process, the existence or not of adsorption process and the number of electrons that is involved in the electrochemical reactions. The resulted said that the reaction of ketoconazole reduction is irreversible, with one definite peaks at 1,44V device phenomenon of reduction do CTZ. The analytical methodology that was developed is fast, sensible and precise, to routine analysis on pills of CTZ. The analytic curve was linear in the concentration area between 1,8 and 5,5.10 6 mol/L, with detection limit 1,7.10 7 mol/L and quantification limit in 5,6.10 7 mol/L.